Marginal microleakage and modified microtensile bond strength of Activa Bioactive, in comparison with conventional restorative materials - Saba Tohidkhah; Hamid Kermanshah; Elham Ahmadi; Behnous Jalalian; Ladan Ranjbar Omrani (Wiley, 2022)
Abstract Objectives This study aimed to assess the enamel and dentin marginal microleakage and dentin microtensile bond strength (μTBS) of ACTIVA BioACTIVE Restorative with and without a bonding agent compared with conventional restorative materials. Material and methods For enamel and dentin microleakage, Class II boxes were prepared in the mesial (1 mm under the cementoenamel junction) and distal (1 mm above the cementoenamel junction) surfaces of 90 extracted human third molars. The teeth were randomly divided into five groups (n = 18): Group Z (G‐Premio Bond + Filtek Z250 XT), Group X (G‐Premio Bond + X‐tra fil bulk‐fill), Group AA (G‐Premio Bond + Activa Bioactive restorative), Group A (Activa Bioactive restorative), and Group G (dentin conditioner + Fuji II LC Improve). The teeth were thermocycled, and their microleakage was quantified using the dye penetration test under a stereomicroscope. For dentin μTBS measurement, 12 specimens were fabricated in metal molds (1 × 1 × 12 mm³) for each group mentioned above, and a universal testing machine measured their μTBS. Data were analyzed using one‐way analysis of variance (ANOVA), the Kruskal-Wallis test, and multiple comparisons tests. Results Significant differences were noted among the groups in marginal microleakage and μTBS (p < .001). The highest mean microleakage scores at the enamel and dentin margins were noted in Group A, which had significant differences with other groups (p < .001). The highest μTBS was found in Group X, with significant differences with Group G and Group A (p < .05). The lowest µTBS was noted in Group A, with significant differences with Groups X, Group AA, and Group Z (p < .001). Conclusions Activa Bioactive without a bonding agent showed significantly lower µTBS to dentin, and higher microleakage at the enamel and dentin margins. Application of adhesive resin with Activa Bioactive provided a dentine bond strength and marginal seal comparable to other restorative materials.